Maternal psychiatric status and infant wheezing: The role of maternal hormones and cord blood cytokines - AY, NADİYE PINAR (WILEY, 2021)
Rationale Maternal psychosocial stress might be associated with development of allergic diseases in the offspring. Objectives To evaluate the association of maternal depression and anxiety with ever wheezing and recurrent wheezing among infants and to assess the role of maternal hypothalamo-pituatary-adrenal axis changes and fetal immune response in this association. Methods This study encompasses two designs; cohort design was developed to evaluate the association of prenatal depression with development of wheezing in infants while nested case-control design was used to assess the role of maternal cortisol and tetranectin and cord blood interleukin 13 and interferon gamma. Results We enrolled 697 pregnant women. Elementary school graduate mother (odds ratio [OR] = 1.5, p = .06), maternal smoking during pregnancy (OR = 3.4, p = .001), familial history of asthma (OR = 2.7, p < .001) increased the risk of ever wheezing. Elementary school graduate mother (OR = 2.6, p = .002), maternal smoking during pregnancy (OR = 4.8, p < .001) and familial history of asthma (OR = 1.7, p = .01) increased the risk of recurrent wheezing. Maternal previous psychiatric disease, or Edinburgh Postnatal Depression Scale or Spielberger State-Trait Anxiety Inventory scores were not associated with wheezing. Maternal tetranectin levels were significantly higher among never wheezers compared to the ever wheezers (264.3 +/- 274.8 vs. 201.6 +/- 299.7, p = .04). Conclusions In conclusion, the major risk factors for ever wheezing and recurrent wheezing were maternal smoking, level of education and family history of asthma. However, maternal depression and anxiety were not determined as risk factors for wheezing. Maternal tetranectin carries potential as a biomarker for wheezing in the infant.
Keywords: fetal programming; maternal depression; tetranectin; wheezing